Membandingkan Kinerja Reksadana Syariah di Indonesia (Periode 2016-2020) - Falahuddin Hasballah; Tinara Rama Dhani; Mukhlis M. Nur; Ahmad Fauzul Hakim Hasibuan; Fuadi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this study was to compare the performance of Islamic equity mutual funds in 2016-2020 using the Sharpe method. Treynor, and Jensen. The method used in this research is descriptive quantitative research. The type of data used is secondary data. From the results of the study found differences in performance values using the three. Using the Sharpe method, almost all Islamic stock mutual funds have negative performance values in 2016-2020. Only the Syariah Mutual Fund Lautandhana, while the Batavia Mutual Fund Syariah Shares have the lowest performance values. Using the Treynor method, the 2017-2020 observation period was all negative, whereas in 2016, the Lautandhana Saham Syariah mutual fund performed positively. Mutual Fund Batavia Dana Saham Syariah has the best performance value, Sucorinvest Sharia Equity Fund has the lowest performance value. Using the Jensen method, during the 2016-2020 observation period, all of them had positive performance values. The Mandiri Investa-Attractive Syariah Mutual Fund has the highest performance value, and the Cipta Syariah Equity Mutual Fund has the lowest performance value.